Turkish Minority and Foreign Policy Stances of Political Parties in Germany - Césarová, Natálie (2019)
The master thesis deals with the issue of the Turkish minority in Germany and with the effect on German political parties with special respect to the Turkish-origin representatives in the German Bundestag after the Federal elections in 2017. The thesis examines the current German-Turkish bilateral relations and their development since the Turkish abortive coup in 2016 to the Erdogan's official visit to Germany. The main aim of the thesis is to examine the question of the ethnicity of the Turkish-origin representatives through the qualitative content analysis focusing mainly on the second generation of German Turks. Additionally, the issue of integration of the Turkish minority into German society is a minor finding in the text. The relevant theory of parliamentary representation is covered in the master thesis. Eventually, the thesis comes up with an applicable theoretical approach to the empirical framework by testing a hypothesis regarding the Turkish minority representation and its ethnicity. The analysis focuses on the period of time from the 2017 Bundestag election on September 24 to the Erdogan’s visit to Germany at the end of September 2018.